The Schmidt Syndrome - Siniscalchi, Carmine; Moretti, Valentina; Cataldo, Simona; Rocci, Anna; Basaglia, Manuela; Tassoni, Maria Ilaria; Quintavalla, Roberto (Acta Biomedica Atenei Parmensis, 2018)
Addison’s disease (AD) is a rare endocrine condition related to adrenal insufficiency. Autoimmune adrenalitis is commonly associated with autoimmune diseases. Autoimmune Addison’s Disease (AAD) describes Autoimmune Polyendocrine Syndrome (APS) in 60% of patients with an important immunitary pathogenesis imprinting. We describes a case of Autoimmune Polyendocrine Syndrome charachterize by adrenal insufficiency and thyroid disease (Schmidt Syndrome). In this case report, Addison’s disease had a slow onset in absence of the typical weight loss. In our considerations this is due to the concomitant hypothyroidism that masked some typical signs and also limited acute presentation.